Pengaruh Kompetensi Kewirausahaan terhadap Minat Berwirausaha pada Mahasiswa Manajemen Angkatan 2017-2019 FEB Universitas Islam Bandung - Khoeru Ilman; Sri Suwarsi; Firman Shakti Firdaus (UNISBA Press, 2023)
Abstract. Human Resource Management refers to the ability of employees that promotes overall economic and social development, including intellectual and physical employability. Human resources do not mean referring only to the human being but to the competence of the individual. One of the factors that determine economic development is the Interest in Entrepreneurship. Interest in Entrepreneurship can be influenced by Entrepreneurial Competence. Entrepreneurial competence in the form of Managerial skills, Conceptual skills, Human skills, Decision making skills, Time managerial skills. This research was conducted on students of the Management study program, Faculty of Economics and Business, class of 2017 – 2019, Bandung Islamic University. This research used quantitative research methods and descriptive analysis. This study used a questionnaire given to 88 respondents. As well as the purpose of this study aims to examine the Effect of Competence on Interest in Entrepreneurship in Management study program students at the Faculty of Economics and Business class of 2017 – 2019 Islamic University. Research data were processed using the SPSS 23.0 application program. The sampling technique is probability sampling. The results of the study found that Entrepreneurial Competence had a positive and significant effect on Interest in Entrepreneurship with a t-count of 6.152 with a significance value of 0.000 less than a significant level of 0.05. The calculated t value is 6.152, which means that it is greater than the t table value (1.98793) for Students of the Management study program, Faculty of Economics and Business, class of 2017 – 2019, Bandung Islamic University. Abstrak. Manajemen Sumber Daya Manusia mengacu pada kemampuan karyawan yang mendorong perkembangan ekonomi dan sosial secara keseluruhan, termasuk kemampuan kerja intelektual dan fisik. Sumber daya manusia tidak berarti hanya mengacu pada manusia tetapi pada kompetensi individu. Faktor yang sangat menentukan pembangunan ekonomi salah satunya adalah Minat Berwirausaha. Minat Berwirausaha dapat dipengaruhi oleh Kompetensi Kewirausahaan. Kompetensi Kewirausahaan berupa Managerial skill, Conceptual skill, Human skill, Decision making skill, Time managerial skill. Penelitian ini dilakukan pada Mahasiswa prodi Manajemen Fakultas Ekonomi dan Bisnis angkatan 2017 – 2019 Universitas Islam Bandung Penelitian ini menggunakan penelitian metode Kuantitatif dan analisis Deskriptif. Penelitian ini menggunakan kuisioner yang diberikan kepada 88 responden. Serta tujuan dari penelitian ini bertujuan untuk menguji Pengaruh Kompetensi terhadap Minat Berwirausaha pada Mahasiswa prodi Manajemen Fakultas Ekonomi dan Bisnis angkatan 2017 – 2019 Universitas Islam. Data hasil penelitian di olah menggunakan program aplikasi SPSS 23.0. Teknik penarikan sampel adalah probability sampling. Hasil dari penelitian ditemukan bahwa Kompetensi Kewirausahaan berpengaruh secara positif dan signifikan terhadap Minat Berwirausaha dengan hasil t hitung sebesar 6,152 dengan nilai signifikansi yang dihasilkan 0,000 lebih kecil dari level of significant 0,05. Nilai t hitung sebesar 6,152 yang berarti lebih besar dari nilai t tabel (1.98793) tehadap Mahasiswa prodi Manajemen Fakultas Ekonomi dan Bisnis angkatan 2017 – 2019 Universitas Islam Bandung.